Discrete-event modelling of the capacity of the toll collection exit point and the formation of congestion. (23rd March 2022) - Talavirya, Alexander; Laskin, Michael
The study addresses the issue of assessing toll plaza (TP) throughput capacity and traffic congestion during toll road operations. To demonstrate a methodology for transport micro-modelling, the western high speed diameter (WHSD) toll road TP in St. Petersburg, Russia, was used as a case study. The discrete-event simulation model of the TP at the toll road exit was developed using AnyLogic software. We accounted for the specifics of traffic composition and user behaviour in the selected urban district. The operation of the TP at low and high traffic flow rates was analysed using the developed simulation model. The empirical data parameters for service time distribution were obtained for each situation. When a TP operates above the threshold throughput capacity, a mathematical method for determining the parameters of the traffic congestion (queue length and time, number of vehicles in the queue) was proposed.